'Your mind is part of your body': Negotiating the maternal body in online stories of postnatal depression on Mumsnet. (March 2021) - Kinloch, Karen; Jaworska, Sylvia
Abstract: This paper looks at the intersection between motherhood and online illness narratives, examining the ways in which women conceptualise their maternal bodies in the context of postnatal depression. Specifically, we examine how discourses of motherhood in distress are positioned in relation to societal norms and expectations, and the othering of the 'imbalanced' maternal body. To do so, we apply corpus assisted discourse analysis to posts made in the Mumsnet Talk forum, which specifically discuss postnatal depression. Our findings highlight the discursive strategies employed to represent embodied experiences of a stigmatised condition in an online forum. We focus particularly on the use of embodied explanatory models for mental ill health in mothers to mitigate the stigma attached to the condition. Our study also shows how the embodied lived experience continually interacts with states of mind when making sense of PND and in doing so, transgresses the boundaries set by the body/mind dualism, which prevails in modern medicine.